Efficacy of prophylactic tranexamic acid among parturient at increased risk for postpartum hemorrhage undergoing cesarean delivery: A systematic review and meta-analyses of randomized controlled trials - Mohamed Aziz Daghmouri; Simon Crequit; Amelie Madeuf; Wael Chaabane; Ortéga Laurent; Patrick Lafforgue; Bechir Azzouzi; Ines Ouaz; Mohamed Ali Chaouch (PLoS ONE, 2025)
Background Postpartum hemorrhage (PPH) remains a significant cause of maternal morbidity and mortality worldwide. Prophylactic pharmacological interventions, especially tranexamic acid (TXA), are under evaluation for their efficacy in preventing PPH during cesarean sections in high-risk women. This systematic review and meta-analysis aimed to assess the effectiveness of prophylactic tranexamic acid among parturients at increased risk for postpartum hemorrhage undergoing cesarean delivery. Methods This systematic review and meta-analysis followed the PRISMA 2020 guidelines and was registered in the PROSPERO database (ID: CRD42024520613). We conducted a comprehensive search in several bibliographic databases for randomized controlled trials comparing prophylactic tranexamic acid to placebo in parturients at increased risk for PPH undergoing cesarean delivery published until 1st, 2024. We sought trials in the United States National Library of Medicine, Cochrane Database of Systematic Reviews (CDSR) and the Cochrane Central Register of Controlled Trials (CENTRAL), Embase, National Institutes of Health PubMed/MEDLINE, Web of Science, and Google Scholar databases. Primary outcomes included intraoperative blood loss, while secondary outcomes covered hemoglobin loss, transfusion needs, the incidence of PPH, and side effects. Results Eleven randomized controlled trials involving 1627 patients were included. The meta-analysis revealed that TXA significantly reduces intraoperative blood loss compared to placebo (Mean Difference (MD) = −343.89, 95% CI [−394.34, −293.43], p < 0.00001). Furthermore, TXA was associated with lower rates of blood transfusions and PPH. The heterogeneity was substantial across studies but reduced significantly in subgroup analyses. No significant differences in side effects, hysterectomy, or additional uterotonic use were observed between the two groups. Conclusions Prophylactic tranexamic acid significantly reduces intraoperative blood loss and the incidence of PPH in parturients at increased risk undergoing cesarean delivery, without increasing side effects. These findings support the broader use of TXA in this high-risk group, although further research is necessary to explore long-term outcomes and optimal administration protocols.